Lung Function Testing On and Off Dopaminergic Medication in Parkinson's Disease Patients With and Without Dysphagia. Issue 2 (4th November 2015) - Sawan, Tareq; Harris, Mary Louise; Kobylecki, Christopher; Baijens, Laura; van Hooren, Michel; Michou, Emilia
Abstract: Background: Swallowing function in individuals with Parkinson's disease (PD) can be negatively affected by dopaminergic medication with associated inhibition of brainstem reflexes. Three different "swallowing‐safety" profiles of PD patients were previously observed, classified according to swallowing safety on and off levodopa. Methods: Here, we investigated the effects ofl ‐dopa on pulmonary function tests (PFTs) on 26 individuals with PD from the three different swallowing‐safety profiles. PFTs results were compared to predicted values and direct comparisons between the groups with or without dysphagia were performed with nonparametric statistical tests (i.e., Kruskal–Wallis). Results: A short (12‐hour) withdrawal froml ‐dopa did not result in any significant changes in PFTs, and no differences on PFTs results were observed between the different dysphagic groups the on and off l ‐dopa state. No correlation was observed between the PFTs results with swallowing safety profiles of PD patients. Conclusions: Although deglutition seems to be at least partially affected by dopaminergic repletion, dopaminergic mechanisms do not seem to be responsible for PD patients' performance in PFTs.